Ground Temperature Property and Restorative Characteristics to Enhance Heat Transfer in GSHP - 高青; 乔广; 于鸣; 李明; 白金玉 (Zhileng xuebao)
Through an intermittent process (GSHP on or off), the ground temperature can be restored to enhance heat transfer in the soil and to decrease the number of wells (such as vertical boreholes) in the Ground Source Heat Pump (GSHP). In the test system of GSHP, both vertical boreholes (100m and 200m) for heat exchangers were established. Some behaviors and Characteristics were investigated, such as the ground temperature distribution in the initial case, the temperature variation in the working condition, and the temperature fluctuation in the intermittent process. Moreover, the investigation on the trend of restorative ground temperature in the intermittent process was emphasized. The intermittent time can change the trend of the temperature, prolong the underground heat transfer and result in the better working condition of GSHP. A method of using intermittent process was presented to make better use of ground source energy and the fact was pointed out that the intermittent controlling technology is very important in the utilization of ground source energy.